How can Cape Flats youth overcome Environmental circumstance by using their Personal potential? - Stoffberg, Max-Gordon (Graduate School of Business (GSB), 2023)
This study focuses on identity and (un)employment among Coloured born-frees from the Cape Flats in Cape Town. Coloured adolescents could be classified as vulnerable because their living conditions are characterized by unemployment, crime, gangsterism and a lack of positive role models. In conjunction with digital exclusion and poor quality education; these circumstances restrict youth from participating fairly in socio-economic activities – effectively limiting their growth potential. Personalization theory states that growth is not solely dictated by environmental conditions but in part dependent on how an individual respond to these external experiences. Most members of the Cape Flats are not criminals or gangsters. However, most research utilizes a deficit paradigm; exclusively emphasizing the negative conditions in these disadvantaged districts. A qualitative Grounded Theory methodology was employed to address this gap by incorporating corporate and creatively employed youth as research participants. Moreover, male and female born-frees, aged 18-28, were interviewed. 10 individuals from each employment sector (corporate, creative and criminal) were given the same set of questions in order to establish reasons why certain careers were chosen. Cognitive and behavioural characteristics, both distinct and shared, across the 3 groups were identified. Personal Potential is derived from Self-actualization and Self-efficacy – this contributes to new knowledge as these theories have not previously been applied to the Cape Flats context. The most destructive influence limiting potential was found to be the behaviour witnessed by others in their neighbourhoods. The findings indicate that communication is the most practical learning tool among youth. However, youth do not want to be told what to do, rather, they want to be like those they see. The innovative praxis model aiding this connection is the digital network Question Mark Kaffy. This platform broadens the outlook of youth beyond what is merely observed in their physical setting, displaying the diversity of South Africa's creatives. This research project sheds light on youth who have maximized their Personal Potential and shares insights as to how others may do the same. Thus, it empowers Cape Flat's creatives to become constructive citizens by serving as new role models to aspiring artists, which contributes to the creation of a Collective Creative Cultural identity amongst Capetonians.